Pulmonary hypertension in the intensive care unit after pediatric allogeneic hematopoietic stem cell transplant: incidence, risk factors, and outcomes - Smith, Michael A.; Cheng, Geoffrey; Phelan, Rachel; Brazauskas, Ruta; Strom, Joelle; Ahn, Kwang Woo; Hamilton, Betty Ky; Peterson, Andrew; Savani, Bipin; Schoemans, Hélène; Schoettler, Michelle L.; Sorror, Mohamed; et al. (Frontiers in Oncology, 2024)
To determine the incidence, risk factors, and outcomes of pulmonary hypertension (PH) in the pediatric intensive care unit (PICU) after pediatric hematopoietic stem cell transplant (HCT).This was a retrospective study of pediatric patients who underwent allogeneic HCT between January 2008-December 2014 at a center contributing to the Center for International Blood and Marrow Transplant Research data registry. Incidence of PH was assessed from PICU diagnostic codes from records merged from the Virtual Pediatric Systems database. Regression and survival analyses identified factors associated with post-HCT PH. Additional post-HCT morbidities and survival after PH were also assessed.Among 6,995 HCT recipients, there were 29 cases of PH, a cumulative incidence of 0.42% (95% CI 0.27%-0.57%) at 60 months post-HCT. In the sub-cohort of 1,067 patients requiring intensive care after HCT, this accounted for a PH prevalence of 2.72% (95% CI 1.74-3.69%). There was an increased risk of developing PH associated with Black/African American race, metabolic disorders, partially HLA-matched or cord blood allografts, graft-versus-host prophylaxis regimen, and lower pre-HCT functional status. Patients who developed PH had significant PICU comorbidities including heart failure, pulmonary hemorrhage, respiratory failure, renal failure, and infections. Survival at 6 months after diagnosis of post-HCT PH was 51.7% (95% CI 32.5%-67.9%).PH is a rare but serious complication in the pediatric post-HCT population. A significant burden of additional comorbidities, procedural interventions, and risk of mortality is associated with its development. Close monitoring and prompt intervention for this severe complication are necessary in this vulnerable population.